Scared, powerless, insulted and embarrassed: hesitancy towards vaccines among caregivers in Cavite Province, the Philippines - Landicho-Guevarra, Jhoys; Reñosa, Mark Donald; Wachinger, Jonas; Endoma, Vivienne; Aligato, Mila F.; Bravo, Thea Andrea; Landicho, Jeniffer; Bärnighausen, Kate; McMahon-Rössle, Shannon A. (BMJ global health, 2021)
Background Several studies have highlighted that vaccine hesitancy (VH) is among the most important threats to global health, especially in low- and middle-income countries, including the Philippines. However, there is a dearth of literature exploring family experiences of—or concerns related to—childhood vaccinations that gives voice to vaccine hesitant caregivers (VHCs) of small children. Here, we present insights from VHCs from the Philippines. - Methods This research draws on in-depth interviews (IDIs) with 44 VHCs who had previously delayed or refused vaccination for their children in rural and urban communities in Cavite Province, the Philippines. Amid the COVID-19 pandemic, we conducted IDIs via an online platform of the respondents’ choosing (ie, Facebook messenger call, Skype and Zoom). All interviews were recorded, transcribed, translated and analysed drawing from the tenets of constructivist grounded theory. We use the social ecological model to structure our results. - Results Among the reasons for delay or refusal of childhood vaccinations, a fear of side effects emerged as the most salient concern, exacerbated by previous negative experiences (including trauma) from a dengue vaccine controversy in 2017. Respondents cited the dengue vaccine controversy as they expressed reluctance (regarding any new vaccines) and suspicion (towards school-based vaccination, the distribution channel used for the dengue vaccine). Heads of households opposing vaccines, perceptions that vaccines are non-essential and influences from the social and traditional media or neighbours contributed to further refusal and delay. Upon probing, VHCs recounted health system concerns particularly with regards to healthcare workers who are sometimes unable to answer their questions and can be dismissive or disrespectful regarding caregivers’ concerns. - Conclusion Understanding VH from the lens of VHCs highlights pathways for interventions to regain trust and bolster confidence towards vaccines. Our findings may serve as linchpins in the development of VH interventions aiming at changing behaviour on a population scale.
Gesehen am 05.11.2021